2014
DOI: 10.1108/jfmm-08-2012-0046
|View full text |Cite
|
Sign up to set email alerts
|

Adaptable apparel: a sustainable design solution for excess apparel consumption problem

Abstract: Purpose – Excess consumption of apparel is driven by the apparel industry to offer more styles at lower prices in shorter time and the consumers’ desire to change fashion. The purpose of this paper is to apply adaptable design in apparel as a sustainable design solution for excess consumption problem. Design/methodology/approach – Guided by sustainable apparel design model C2CAD, two adaptable apparel prototypes for female college studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…The global textile fibre production, consumption of textiles and amount of textile waste are constantly growing (Dahlbo et al , 2017). The clothing industry offers more styles at lower prices in shorter time cycles and the consumers desire to change their style (Cao et al , 2014). Fast fashion is a successful and increasingly prevalent business model in which fashion retailers create cheap, throwaway goods at much lower costs and have multiple seasons instead of the traditional two collections per year (Birtwistle and Moore, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The global textile fibre production, consumption of textiles and amount of textile waste are constantly growing (Dahlbo et al , 2017). The clothing industry offers more styles at lower prices in shorter time cycles and the consumers desire to change their style (Cao et al , 2014). Fast fashion is a successful and increasingly prevalent business model in which fashion retailers create cheap, throwaway goods at much lower costs and have multiple seasons instead of the traditional two collections per year (Birtwistle and Moore, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…There are several ways to decrease inconsistency between sustainability and fashion. Cao et al (2014) found out that consumers would keep and use adaptable garments for a long time and buy fewer new ones when they were able to utilise the same garments in different ways. Alongside fast fashion, the so-called slow fashion has become a more popular, socially conscious movement that shifts consumers’ mindsets from quantity to quality.…”
Section: Introductionmentioning
confidence: 99%
“…Gam, Cao, Farr, and Heine (2009) applied the cradle-to-cradle design model (McDonough & Braungart, 2002) in apparel to develop a sustainable apparel design and production model C2CAD, and implemented the model in children's knitwear design and production. Sustainable design strategies used in other industries, including the automotive industry, such as design for disassembly and adaptable design were also applied in apparel design and development (Cao et al, 2014;Gam, Cao, Bennett, Helmkamp, & Farr, 2011). Key areas of research regarding social responsibility have focused on measures to improve working conditions in apparel production, including adoption and enforcement of codes of conduct, development of internal policies, practices, and accountability mechanisms; improvement of wages; increased transparency and public reporting, and improved buyer-supplier partnerships (Dickson, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Gam [1] found that women with at least one child are interested in sustainable and eco-friendly products that are beneficial for their children, which also inspires parents to act in an environmentally responsible manner. Previous researches mainly focused on design strategies for multifunctional clothing concerning sustainable development in the fashion market [2][3][4][5]. The design of multifunctional clothing incorporates the application of ergonomic concepts and in-depth analysis of aesthetics and practicality to achieve the objectives of children's clothing and to promote harmonious growth in society.…”
Section: Introductionmentioning
confidence: 99%